State-of-the-Art Design and Optimization of Strain Gauge-Type Load–Displacement Transducer for in In Situ Nanoindentation Systems - Duhui Lu; Jianliang Liu; Mukai Wang; Sen Gu (Sensors)
Force–displacement transducers are key components in in situ nanoindentation systems. The current existing capacitance-type transducers adopted in state-of-the-art commercial in situ nanoindentation systems are restricted by limited maximum ranges, and strain gauge-type transducers in the current in situ nanoindentation systems have the limitation of low resolution and high values of mass. In the paper, we propose a mechanical design and improvement of a low-mass strain gauge-type force–displacement transducer capable of performing high resolution in situ nanoindentation measurements. The transducer mainly consisted of a parallelogram-shaped flexure hinge and two strain gauges. Air resolution, in situ resolution, and mass experiments reported an air force resolution of 5 μN, an in situ force resolution of 5 μN inside a scanning electron microscope (SEM), and a mass of 6.53 g of such a strain gauge-type load–displacement transducer. Then, the transducer was assembled into a newly developed in situ nanoindentation–atomic force microscope (AFM) hybrid system and a newly developed in situ nanoindentation system. The proposed design successfully performed nanoindentation measurements inside SEM. Based on the results, the proposed strain gauge-type transducer shows great advantages compared to the current state-of-the-art transducers.